The Binding Force and Corrosion Resistance of Ni - TiN Composite Coating by Ultrasound - Assisted Pulse Electrodeposition - SUN Chui - kang, JIA Wei - ping, ZHOU Shao - an, YU Wei - wen (Cailiao Baohu)
Ultrasound - assisted pulse electrodeposition is a preferred method for producing nanocomposite coating, with combining the effects of ultrasonic acoustic cavitation which benefited de - agglomeration and agitation effects, and the characters of pulsing current such as high instantaneous current density, flexible control of current parameters. In this work, Ni - TiN nanocomposite coatings were successfully deposited by ultrasonic - assisted pulse electrodeposition method. The microstructure, binding force and corrosion resistance of Ni - TiN composite coatings were investigated through scanning electron microscopy (SEM), energy dispersive spectroscope (EDS) analysis system, Vickers microhardness testing, scratch tester and electrochemical workstation. Results showed that TiN content of composite coating was affected by the parameters of current density, pulse duty cycle and ultrasonic power. Under the conditions containing 4 A/dm2 of current density, 40% of duty cycle, 300 W of applied ultrasonic power, the as - prepared composite coatings possessed 9.98%(mass fraction) of TiN particles, 741 HV of microhardness, the surface grains of the composite coating were fine, smooth and compact, and the coating had a good adhesion to the substrate with 704.77 MPa of binding force. In addition, the composite coating performed better corrosion resistance.